PENGARUH PENGAJARAN TUTOR SEBAYA DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN KOTA SOLOK - Julia M, Trisna; Zulfaneti, Zulfaneti; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was conducted for the studentsâ low understanding on mathematics concept. This purpose of the research was to study whether the mathematics conceptual understanding of the students taught by using Peer-Tutoring teaching assisted with a quiz was better than that of students taught by using conventional learning in class VIII of MTsN Kota Solok. This was an experimental research which used random toward the subject design. The instrument of the research was a test on conceptual understanding. The data gained was analyzed by using t-test. Based on the result of data analysis, it was found that the two classes were normally distributed and homogenous on the level of significance Î± = 0,05. The result of the hypothesis test showed that the value of tcalculated (3,7) was higher than ttable (1,709) indicating that the hypothesis was accepted. Based on the these result, it was concluded that the mathematics conceptual understanding of the students taught by using Peer-Tutoring teaching assisted with a quiz was better than that of students taught by using conventional learning in class VIII of MTsN Kota Solok.